Hydrophobic and hydrophilic balance and its effect on mesophase behaviour in hydroxyalkyl ethers of methyl glucopyranoside - Singh, Madan K.; Xu, Rui; Moebs, Sylvie; Kumar, Anil; Queneau, Yves; Cowling, Stephen J.; Goodby, John W. (Chemistry-A European Journal, 2013)
Four series of monosubstituted methyl -D-glucopyranoside hydroxyalkyl ethers were prepared and their thermotropic and lyotropic self-organising properties were investigated in terms of the hydrophobichydrophilic balance with respect to their molecular structures. The results obtained lead us to a new understanding of the forces that drive the formation of condensed soft-matter phases.
Keywords: carbohydrates; liquid crystals; mesophases; Self-assembly; soft matter

Conjunctive photoluminescence enhancement through plasmonic and photonic band-gap pathways in a chiral self-assembled system - Baral, Marlin; Krishna Prasad, S.; Bhat, Sachin A.; Nayak, Rashmi A.; Yelamaggad, C. V. (ChemPhotoChem, 2020)
We describe two parallel pathways for enhancing the intrinsic photoluminescence of an organic emitter dispersed in a liquid crystal (LC) medium. The pathways have independent origins: (i) Metal enhanced fluorescence (MEF) incorporating gold nanoparticles having an organic shell of pro-mesogenic cholesterol esters; and (ii) Matching the photonic band gap (PBG) due to the helical structure in a self-assembled chiral system with the excitation wavelength. This unprecedented combination of both pathways achieves a level of photoluminescence exceeding the sum of the contribution from the individual methods. This conjunctive protocol results in an overall enhancement by a factor of 37 between the emitter dispersed in a non-chiral LC and that appealing to both MEF and PBG pathways. Circular polarized luminescence measurements also show that this protocol helps in effective discrimination of chiral light achieving a large dissymmetry factor whose magnitude (+0.33) is comparable to the highest recorded to date. Electric field switching between two states is also shown to result in appreciable fluorescence modulation. Being generic in nature the protocol employed can be adapted to a variety of situations with the large magnitude as well the modulation level suitable for applications such as biosensors, various analyte detection, and other photonic devices.
Keywords: chirality; circularly polarized luminescence; liquid crystals; photonic band-gap; plasmonics

Wide thermal range, exclusive occurrence of technically significant chiral nematic phase: synthesis and mesomorphism of cholesterol-based non-symmetric dimers - Nayak, Rashmi Ashwathama; Bhat, Sachin A.; Rao, D. S. Shankar; Yelamaggad, V. C. (Bulletin of Materials Science, 2020)
Fifteen new non-symmetric chiral dimers belonging to three different series have been synthesized and evaluated for their mesomorphic properties. They are formed by interlinking cholesterol with salicylaldimine (SAN) cores (with reverse imine groups) via an omega-oxyalkanoyloxy spacer. Within a series, the length of the terminaln-alkoxy tails has been varied for a fixed even-parity spacer. Three even-parity spacers such as 4-oxybutanoyloxy, 6-oxyhexanoyloxy and 8-oxyoctanoyloxy have been used to join two cores, whereas the terminal tails such asn-butyloxy,n-hexyloxy,n-octyloxy,n-decyloxy andn-dodecyloxy chains have been attached to the SAN core. Microscopic and calorimetric experimental results show that all the dimers behave identically exhibiting the chiral nematic (N*) phase solely, which was authenticated by powder X-ray diffraction studies carried out on some selected samples. In the vast majority of the cases, this phase is thermodynamically stable, and while cooling, it exists over a wide thermal range covering room temperature (RT) due to supercooling. This finding is notable given the fact that the N* phase possesses technologically significant optical properties. At RT, the N* phase displayed one of the iridescent colours characteristically caused by interference and diffraction of the reflected and scattered light. A comparative study reveals that the lengths of both the terminal chain and central spacer influence the clearing temperature of the dimers, and also the temperature range of the N* phase. The selective reflection measurements revealed that the pitch of the N* phase is either temperature sensitive or temperature insensitive. Temperature-dependent circular dichroism (CD) spectra were recorded for the planar texture of the N* phase formed by a dimer, as a representative case. The presence of an intense negative CD band suggests the left-handed screw sense of the N* phase helix.
Keywords: CD activity; cholesteric phase; dimers; liquid crystals; selective reflection

Elliptically birefringent chemically tuned liquid crystalline nanocellulose composites for photonic applications - Singh, Shiva; Bhardwaj, Shakshi; Verma, Chhavi; Chhajed, Monika; Balayan, Kajal; Ghosh, Kaushik; Maji, Pradip K. (Journal of Molecular Liquids, 2022)
Cellulose nanocrystals (CNCs) based photonic materials are one of the promising materials in the recent trends. The liquid crystalline behavior of the CNCs can be tailored to different advanced applications. The proposed research investigates the potential of CNCs as an optically active material. CNCs were tuned to hydroxypropyl nano cellulose (HPNC) with the degree of substitution 1.39. The prepared liquid crystalline HPNC were dispersed in various concentrations of monomethyl ether of polyethylene glycol to get waterborne materials with specific optical anisotropy. The extraction, modification, and morphology of the CNCs were investigated using NMR (Nuclear Magnetic Resonance), TEM (Transmission Electron Microscopy), XRD (X-ray Powder Diffraction), and FESEM (Field Emission Scanning Electron Microscopy) analysis. The prepared HPNC was analyzed using a hot stage POM (Polarized Optical Microscope) for optical anisotropy. The thermal stability of prepared CNCs and HPNC was also investigated. Upon optimization using rheology and POM, it was found that at the ratio of 1:1, HPNC (5 wt%) and mPEG (40 wt%) had the most distinct optical properties. The potential of the prepared materials can be further explored in sensing, smart coating, and security materials. (C) 2022 Elsevier B.V. All rights reserved.
Keywords: bagasse; Cellulose nanocrystals; Elliptical birefringence; liquid crystals; optical anisotropy

Vastly increased mesophase range due to superstructure formation from in situ prepared gold nanoparticles with liquid crystalline ligands: toward enhanced optoelectronic applications - Duggal, Muskan; Khatavi, Santosh; Yelamaggad, Channabasaveshwar V.; Shankar Rao, Doddamane Sreenivasamurthy; Krishna Prasad, Subbarao; Prasad, Bhagavatula L. V. (ACS Applied Nano Materials, 2025)
Gold nanoparticle (Au NP)-liquid crystal (LC) composites have gained considerable interest in developing cutting-edge electro-optical materials. This study introduces an innovative synthetic approach that significantly augments the capabilities of Au NP-LC composites by utilizing an amine-functionalized LC as both a reducing and capping agent in the refined Brust-Schiffrin method. In its standard form, this method yields Au NP-LC composites with appealing features like improved clearing temperature. However, the optical characteristics do not display any additional features and resemble simple LC-ligand functionalized Au NP, attributed here to the surplus LC employed to obtain the dual capabilities of reduction and capping. Thus, it was gratifying to observe a dramatic enhancement in mesophase stability with the removal of just a few percentages of excess LC, which is attributed to a remarkable and unprecedented one-dimensional superstructure formation. Furthermore, the removal of surplus LC caused the composite to exhibit Fano-like resonance in the UV-vis spectrum, a noteworthy optical feature likely resulting from dynamic plasmonic interactions, including plasmon-polariton interactions and lattice plasmon modes. Thus, the simple yet robust protocol employed yields Au NP-LC composites with an ultrawide thermal range of the mesophase that paves the way for realizing next-generation electro-optic materials featuring enhanced performance and response.
Keywords: Fano-resonance; gold nanoparticles; liquid crystals; nanosoftcomposites; superstructure